College Students’ Attitudes Toward Immigration within the United States - Lee, Walker V. (My University, 2021)
A common debate in today’s college classrooms center around immigration, and it is a current social issue within the United States. It is important to understand college students’ attitude on immigration as they will be the ones to address the issue in the future. In this paper, I attempt to understand southeastern college student’s attitudes toward immigration by looking at demographic information and how this information influences college student’s attitude on immigration. Based on this assumption, the study will attempt to discover if you can predict certain immigration opinions based on demographic information. By using surveys, the study attempts to reach conclusions on these goals. Chi squares and ordinal regression test were used as forms of data analysis to come to conclusion for the research goals.
Chapter 1: Introduction 1 -- Chapter 2: Literature Review 4 -- Chapter 3: Methods 23 -- Chapter 4: Results 27 -- Chapter 5: Discussion 35 -- Chapter 6: Conclusion 38
Keywords: Academic theses; College students--Attitudes; Emigration and immigration--Social aspects; Emigration and immigration; Immigrants